2013
DOI: 10.1124/dmd.113.053025
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Sinusoidal Efflux from the Liver Is Consistent with Negligible Biliary Excretion and Absence of Enterohepatic Cycling

Abstract: Although metformin hepatic distribution is critical to pharmacological activity, the drug is cleared by urinary excretion. Metformin hepatobiliary disposition was studied in rodents representative of clinical pharmacokinetics to elucidate why metformin is not appreciably eliminated in bile. On average, 1.0% 6 0.1% of the metformin oral dose was present in the liver (liver/plasma ratio = 4.5 6 0.6) over a pharmacologically relevant dose and time range in mice (10-300 mg/kg; 1.5-2.5 hours; T max = 1.4 6 0.5; bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
(56 reference statements)
2
25
0
Order By: Relevance
“…This difference is consistent with the presence of other distributional compartments for metformin in vivo, including the small intestine, kidney, liver, and skeletal muscle (Wilcock and Bailey, 1994;Scheen, 1996). Distribution into these organs is a carrier-facilitated process, and thus distributional equilibrium is achieved faster in vivo (Gong et al, 2012;Zamek-Gliszczynski et al, 2013a). Although metformin tissue distribution does not stand out as particularly high individually [e.g., kidney/plasma ratio: 11.9 6 1.1; and liver/ plasma ratio: 4.5 6 0.6 in mice (Zamek-Gliszczynski et al, 2013a)], collectively these additional sites of distribution contribute to the higher partitioning rate observed in vivo.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This difference is consistent with the presence of other distributional compartments for metformin in vivo, including the small intestine, kidney, liver, and skeletal muscle (Wilcock and Bailey, 1994;Scheen, 1996). Distribution into these organs is a carrier-facilitated process, and thus distributional equilibrium is achieved faster in vivo (Gong et al, 2012;Zamek-Gliszczynski et al, 2013a). Although metformin tissue distribution does not stand out as particularly high individually [e.g., kidney/plasma ratio: 11.9 6 1.1; and liver/ plasma ratio: 4.5 6 0.6 in mice (Zamek-Gliszczynski et al, 2013a)], collectively these additional sites of distribution contribute to the higher partitioning rate observed in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…Metformin is eliminated rapidly and efficiently by the kidneys, the sole clearing organ for this drug (Glucophage, 2009). Metformin's renal extraction ratio is 90%-100% in mice, rats, and humans (plasma renal clearance approximates renal plasma flow rate) (Davies and Morris, 1993;Choi et al, 2006;Glucophage, 2009;Higgins et al, 2012;Zamek-Gliszczynski et al, 2013a). Relative to the 6.2-hour plasma half-life in humans, the half-life of repartitioning from the cellular component of blood to plasma is 6-fold longer (Table 2), resulting in a longer in vivo whole-blood half-life of 17.6 hours and an even longer in vivo erythrocyte half-life of 23.4 hours (Robert et al, 2003;Glucophage, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT-mediated transport is generally considered electrogenic and independent from sodium. The primary driving force is supplied simply by the electrochemical gradient of the transported compounds or the electronegative membrane potential (Klaassen and Aleksunes, 2010;Zamek-Gliszczynski et al, 2013). However, in recently published studies OCT-mediated transport was also described to occur via cation exchange (Budiman et al, 2000;Pelis et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Recent experimental data in animals showed that metformin sinusoidal efflux from the liver is consistent with negligible biliary excretion and absence of enterohepatic cycling [24].…”
Section: Biguanides (Metformin)mentioning
confidence: 99%